Determinants of Antenatal Care Utilization at Batua Health Center, Makassar City: A 2024 Study - St. Rosmanely; Nurhayani Nurhayani; Muhammad Alwy Arifin; Zaskiah Zaskiah (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2025)
Introduction: Coverage of antenatal care services visits at Batua Health Centre will fluctuate in 2023. The causal factors include predisposing factors, enabling factors and need factors, our objective was to determine the factors related to the utilization of antenatal care services for pregnant women in the working area of the Batua Health Centre in 2024. Methods: This research uses a quantitative type of research, with a cross-sectional study approach. The population in this study were all pregnant women who had visited K4 at the Batua Health Center, namely 80 pregnant women. The sample in this study used a total sampling of 80 pregnant women with the sample criteria being pregnant women in the third trimester of pregnancy. The analysis technique uses univariate and bivariate tests in the form of Fisher's exact test using statistical test applications. Results: This research shows that there is a significant relationship between education (p=0.039<0.05), employment (p=0.003<0.05), knowledge (p=0.009<0.05) and husband's support (p=0.021<0.05) with the utilization of antenatal care services for pregnant women in the working area of Batua Health Center in 2024, while there is no significant relationship between age (p=0.551>0.05) and accessibility (p=0.053>0.05) with utilization of antenatal care services for pregnant women in the working area of the Batua Health Center in 2024. Conclusion: Education, employment, knowledge, and husband’s support play a crucial role in the utilization of ANC services among pregnant women. These findings underscore the importance of targeted interventions, such as community-based maternal health education programs and policies that promote husband involvement in maternal health support. To enhance ANC service coverage and effectiveness, strategic measures should be implemented, including strengthening maternal health awareness programs, providing broader access to health information, and optimizing the role of healthcare workers in encouraging regular ANC visits. The Batua Health Centre is encouraged to collaborate with local policymakers to develop strategies that improve awareness and participation in ANC services, ultimately contributing to better maternal and neonatal health outcomes on a broader scale.